METHODS OF IMPLEMENTING INTERDISCIPLINARY INTEGRATION OF MATHEMATICAL SCIENCES IN HIGHER EDUCATION INSTITUTIONS - Xakim Murtazaqulovich Xudoyberdiyev (European Science Publishing, 2025)
This article explores the methods of implementing interdisciplinary integration of mathematical sciences within higher education institutions, with a focus on economics-oriented universities in Uzbekistan. In the context of educational modernization and digital transformation, there is an increasing demand for integrating mathematics with other academic disciplines to enhance the practical relevance of knowledge. The study discusses strategies that connect mathematical concepts with economic modeling, data analysis, finance, and management subjects, thereby promoting holistic thinking and applied learning. Drawing on both theoretical insights and practical experiences, the paper evaluates the effectiveness of curriculum alignment, collaborative teaching, and digital platforms in fostering interdisciplinary competencies. The article aims to contribute to the development of an integrated educational model that responds to contemporary labor market needs and supports innovation in teaching practices.
Keywords: Interdisciplinary integration, mathematical sciences, higher education, economics education, curriculum design, applied mathematics, Uzbekistan, educational innovation, digital transformation, competency-based learning.